Effects of microvibration stimulation on developmental potential of discarded germinal vesicle oocytes of human - Liu, Qinli; Zhao, Sen; Zhou, Jian; Liu, Ping; Huo, Bo (Frontiers in Endocrinology, 2022)
Objective: This research aims to study the effects of continuous microvibration stimulation on the parthenogenetic development of human germinal vesicle oocytes. Methods: Ninety-five discarded immature oocytes from intracytoplasmic sperm injection treatment (ICSI) cycles performed at Amcare Women’s & Children’s Hospital between January and December 2021 were used for conventional static culture as well as 10 Hz microvibration culture. We investigated the differences between the two groups in terms of oocyte maturation rate, parthenogenetic activation rate, and parthenogenetic blastocyst formation rate. Results: The static culture and 10 Hz microvibration culture of 95 oocytes showed that the parthenogenetic blastocyst formation rate in the microvibration culture group was significantly higher than those in the traditional static culture group. Conclusion: A continuous microvibration stimulation can significantly improve the parthenogenetic developmental potential of human immature oocytes.